Assessing Students’ Speaking Skills at 2nd Semester Students of English Study Program IAIN Curup - Desfitranita, Desfitranita; Senjahari, Bayu (ENGLISH FRANCA : Academic Journal of English Language and Education, 2019)
Speaking skill in English language learning is sometimes difficult for learners. Some students in second semester in IAIN Curup at English study program experienced errors in daily communication. This research tried to disclose what errors that the students did, to what extent the errors occurred. Qualitative approach was considered appropriate in this research because it did not try to generalize the findings but to deepen the case. Observation and open-ended Interview were applied to gather the data. As the instruments, field notes and voice recorder were utilized. The result shows that the students made errors in the four categories namely error in the using of be + adjectives, misplace be ‘present time’ and ‘past time, missing verbs and error in applying preposition. Errors occurred in the circumstances of choosing sentence verbs time signal and the lack of awareness in placing ‘be’ for a sentence. Keywords: Speaking errors, grammar, sentence construction